2018
DOI: 10.1080/09658211.2018.1545858
|View full text |Cite
|
Sign up to set email alerts
|

False memories in music listening: exploring the misinformation effect and individual difference factors in auditory memory

Abstract: False memories in music listening: Exploring the misinformation effect and individual difference factors in auditory memory The study of false memory has had a profound impact on our understanding of how and what we remember, as shown by the misinformation paradigm (Loftus, 2005). Though misinformation effects have been demonstrated extensively within visual tasks, they have not yet been explored in the realm of non-visual auditory stimuli. Thus, the present study aimed to investigate whether post-event inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…The results highlight the relationship that listeners have with particular artists as a driving force when describing and making judgments about music. It has previously been shown that the perceived prestige of the artists of a track can change the judgements people make about the same musical pieces when they are told they are different [21]. A performer's status can bias the evaluation of musical stimuli [38] and empathy with an artist was found to be an important factor in aesthetic experiences of music and poetry [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results highlight the relationship that listeners have with particular artists as a driving force when describing and making judgments about music. It has previously been shown that the perceived prestige of the artists of a track can change the judgements people make about the same musical pieces when they are told they are different [21]. A performer's status can bias the evaluation of musical stimuli [38] and empathy with an artist was found to be an important factor in aesthetic experiences of music and poetry [39].…”
Section: Discussionmentioning
confidence: 99%
“…Much of the research reviewed so far has either presented participants with experimenterselected music or asked people to report preferred styles, recreate memories of their favourite music, or talk about the music they like. One main drawback of these approaches is that participants either have no choice of musical stimulus or they are relying on memory which, although sometimes vivid [19,20], is not always accurate [21]. A more robust way of exploring preference is to focus on people's own music collections.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, despite the popularity of behavioural economics, the field has not yet been applied explicitly to the study of judgements and decision-making processes in the context of music listening and music-related phenomena. Thus, the behavioural economics of music (Anglada-Tort & Müllensiefen, 2017;Anglada-Tort, Baker, & Müllensiefen, 2018;Anglada-Tort, Steffens, & Müllensiefen, 2018) aims to create a solid understanding of the role that behavioural economics and the psychology of decision making can play to study music judgements, choice behaviour, and aesthetics. In the present study, we applied field research methodology commonly used by behavioural scientists and experimental economists to investigate donating behaviour and charitable giving in the real world (e.g., Ebeling et al, 2017;Ekström, 2012;Khadjavi, 2016;Moussaoui et al, 2016;Olda & Ichihashi, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in the memory domain, the presence of post-event misinformation about a given music piece can impair listeners' ability to remember the music (Anglada-Tort, Baker, & Müllensiefen, 2018).…”
Section: The Impact Of Contextual Information On Subjective Evaluationsmentioning
confidence: 99%